Modeling and Behavior Rehearsal to Improve Communication Skills in Adolescent with Language Disorder - Kurniandini, Priskila; Yoenanto, Nono Hery (Jurnal Psikologi Teori dan Terapan, 2024)
Background: Adolescents with language disorder have significant language difficulties in many situations and impact their communication skills. Communication difficulties experienced by adolescents with language disorders can increase the risk of feeling anxious in social situations and having fewer peer relations. Therefore, interventions are needed that can optimize communication skills. Objective: The aim of this research is to find out whether modeling and behavior rehearsal can improve communication skills in adolescent with language disorder. Method: This research is a quantitative research that uses single subject ABA design. The participant is a 14-year-old girl with language disorder. There are 4 skills that are taught & observed, such as giving comments, asking relevant questions, asking the other person's opinion, and paying attention to the other person's attitude while speaking. Results: All communication skills is increasing, including ask the other person's opinion and provide comments that match with the topic. Conclusion: This proves that modeling and behavior rehearsal are effective in improving adolescent's communication skills with language disorder.AbstrakLatar Belakang: Remaja dengan language disorder memiliki hambatan yang signifikan dalam berbahasa di berbagai situasi dan itu berdampak pada kemampuan komunikasi. Kesulitan berkomunikasi yang dialami remaja dengan language disorder dapat meningkatkan risiko merasa cemas dalam situasi sosial dan memiliki sedikit relasi teman sebaya. Karena itu, dibutuhkan intervensi yang bertujuan untuk mengoptimalkan kemampuan komunikasi saat berinteraksi sosial, seperti bertanya dan memberi komentar. Tujuan: Tujuan penelitian ini adalah untuk mengetahui apakah penerapan teknik modeling & behavior rehearsal dapat meningkatkan kemampuan komunikasi pada remaja yang mengalami language disorder. Metode: Penelitian kuantitatif dengan desain single subject research ABA. Partisipan merupakan remaja perempuan berusia 14 tahun dengan language disorder. 4 target perilaku yang diobservasi yaitu memberi komentar, bertanya hal yang relevan, menanyakan pendapat lawan bicara, dan memperhatikan sikap lawan bicara saat berbicara. Hasil: Adanya peningkatan pada kemampuan menanyakan pendapat lawan bicara dan memberikan komentar yang sesuai topik pembicaraan. Simpulan: Teknik modeling dan behavior rehearsal efektif meningkatkan kemampuan komunikasi remaja dengan language disorder.